Confounding influence of tamoxifen in mouse models of Cre recombinase-induced gene activity or modulation - Hammad, Seddik; Meyer, Christoph; Dewidar, Bedair; Werle-Urban, Julia; Nwosu, Zeribe C.; Dormann, Christof; Gao, Yan; Gould, Kerry; Han, Mei; Yuan, Xiaodong; Ebert, Matthias; Dooley, Steven (Archives of toxicology, 2018)
Tamoxifen (TAM) is commonly used for cell type specific Cre recombinase-induced gene inactivation and in cell fate tracing studies. Inducing a gene knockout by TAM and using non-TAM exposed mice as controls lead to a situation where differences are interpreted as consequences of the gene knockout but in reality result from TAM-induced changes in hepatic metabolism. The degree to which TAM may compromise the interpretation of animal experiments with inducible gene expression still has to be elucidated. Here, we report that TAM strongly attenuates CCl4-induced hepatotoxicity in male C57Bl/6N mice, even after a 10 days TAM exposure-free period. TAM decreased (p < 0.0001) the necrosis index and the level of aspartate- and alanine transaminases in CCl4-treated compared to vehicle-exposed mice. TAM pretreatment also led to the downregulation of CYP2E1 (p = 0.0045) in mouse liver tissue, and lowered its activity in CYP2E1 expressing HepG2 cell line. Furthermore, TAM increased the level of the antioxidant ascorbate, catalase, SOD2, and methionine, as well as phase II metabolizing enzymes GSTM1 and UGT1A1 in CCl4-treated livers. Finally, we found that TAM increased the presence of resident macrophages and recruitment of immune cells in necrotic areas of the livers as indicated by F4/80 and CD45 staining. In conclusion, we reveal that TAM increases liver resistance to CCl4-induced toxicity. This finding is of high relevance for studies using the tamoxifen-inducible expression system particularly if this system is used in combination with hepatotoxic compounds such as CCl4.